Kenneth O. Morgan : my histories. - Morgan, Kenneth O. ([Cardiff] : University of Wales Press, 2015)
The eventful life, scholarly work and political and personal experience of Wales's leading historian, reflecting on the challenges and achievements which have peppered his long and successful career.
Cover; Back Cover; Foreword; List of illustrations; 1 A Divided Consciousness; 2 Education, Education, Education; 3 History-Making: A Welsh Historian; 4 History-Making: A British Historian; 5 History-Making: A Labour Historian; 6 History-Making: A Contemporary Historian; 7 History-Making: A Biographer; 8 Experiences: The House of Lords; 9 Experiences: Travelling; 10 Experiences: Old and New Labour; 11 My History; Appendix; Index
Vendor-supplied metadata.
eBooks on EBSCOhost
Keywords: Morgan, Kenneth O; Historians -- Wales -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Study & Teaching; BIOGRAPHY & AUTOBIOGRAPHY -- Political; Historians; Wales; autobiographies (literary works); Autobiographies; Biographies; Autobiographies; Biographies; Autobiographies; Biographies